Penanganan Awal pada Berbagai Jenis Luka Akut - Nuridah Nuridah; Yuniarti Ekasaputri Burhanuddin; Yodang Yodang (Jurnal Abdimas Kesehatan (JAK), 2023)
Injuries that often cause injuries often happen to anyone and anywhere, and it is not uncommon for wounds to be difficult to heal and even become scars that cannot be removed due to ineffective wound care. The role of health educators is by providing education in community service activities through the practice of "early treatment of various types of wounds". The purpose of this service is to educate youth in increasing understanding regarding the proper handling of wounds. This activity was carried out in the Wihdatul Ummah Kolaka IT SMA school environment on Monday, December 12, 2022, which was attended by 27 student representatives and 5 teachers and staff in the form of practice groups using materials and consumables for wound care. With the education provided through wound care practices, students are able to properly practice how to care for various types of wounds and are able to understand properly the proper management of wound care.